Effects of Fe substitution on the transport properties of the superconductor MgB2 - Gahtori, Bhasker; Lal, Ratan; Agarwal, S. K.; Kuo, Y. K.; Sivakumar, K. M.; Hsu, J. K.; Lin, J. Y.; Rao, Ashok; Chen, Soo Kien; MacManus Driscoll, Judith L. (American Physical Society, 2007)
A systematic study has been made on the effect of Fe substitution by means of resistivity, thermal conductivity, and Seebeck coefficient of the Mg1−xFexB2 superconductor involving 0%, 0.3%, 0.6%, 1.2%, and 3.0% Fe content. The superconducting transition has been found to be very sharp 0.2 K for a pristine sample and substitution of Fe results in the decrease of TC with the increase in the transition width. Thermal conductivity is found to decrease with Fe content in general, such that the shoulder present in the pristine sample tends to fade away with increasing Fe. An analysis has been made on the normal state resistivity in terms of a two-band model, and of the thermal conductivity in terms of the Wiedemann-Franz law and the lattice thermal conductivity,and the information obtained on the basis of this analysis has been discussed. Besides, the electronic density of states DOS near the Fermi level remains nearly unaffected upon Fe substitution, as evidenced by the Seebeck coefficient measurements. When compared with Mn, Fe behaves like a nonmagnetic element with a modest variation in TC and on the other hand, the TC depression is much stronger when compared with other elements like Al, Cu, etc. Therefore, the observed variation in TC for the presently investigated concentrations of Fe is attributed to the specific nature of the given substituent element Fe in altering the phonon frequency and/or electron-phonon coupling strength rather than spin-flip scattering or change in DOS or disorder.